Denotative and Connotative Meaning in Pamungkas Song Lyric “Queen of the Hearts”: English - Farhan Mulyadin Satria Dharma Mulyadin (Journal of Classroom Action Research, 2023)
A Song lyrics as a part of literary works is basically an art of language use. Song lyrics can be used by musicians to express their ideas, thoughts, feelings and emotions in the form of artistic words. The object of this research is a song lyric by a famous musician, namely Rizki Rahmahadian Pamungkas or better known by the stage name Pamungkas. Pamungkas is a singer, songwriter and also known as a music producer and have their music producer company namely maspam records that produce other great musician like; Oslo Ibrahim, Prince Husein and Morad. Pamungkas born in Jakarta 14th April 1993 known to be great musician who already has 4th albums and one rearrangement album such; Walk the Talk, Flying Solo, Solipsism 0.1, Solipsism 0.2 and the one that was recently released is birdy. One of his famous song was Queen of the heart that will be the object in this research which searching of connotative and denotative. This research uses descriptive qualitative methods and theory uses in this research is semiotics theory of Roland Barthes which is focused on a denotative and connotative meaning in Queen of the Hearts song. The result of this research show that several denotative and connotative meaning in Queen of the Hearts song like, “queen of the heart” queen, means and independent women ruled something that mentioned in this song which is heart. Because of that reasons, the researcher interested researching connotative meaning in Pamungkas’ song lyrics. Keywords: Denotative. Connotative. Pamungkas. Semiotics